Improving the transparency and reliability of observational studies through registration - Naudet, Florian; Patel, Chirag J; DeVito, Nicholas J; Le Goff, Gérard; Cristea, Ioana A; Braillon, Alain; Hoffmann, Sabine (BMJ (Online), 2024)
Florian Naudet and colleagues argue that routine registration of observational research is needed and suggest how current processes can be adapted to facilitate it